2011
DOI: 10.2478/v10172-011-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Studies Into New, Environmentally Friendly Ag-Cu-Zn-Sn Brazing Alloys of Low Silver Content

Abstract: The paper present selected results of the research conducted for elimination of toxic cadmium from silver based brazing alloys of Ag-Cu-Zn-Cd type. The investigations were conducted with nine new alloys of constant, low silver content (25%) and diversified copper (38.8-46%), zinc (19-32%) and tin (3-10%) contents. Tin was selected as potentially the best cadmium substitute basing on literature review and analysis of equilibrium systems.For examinations and tests a series of ingots in laboratory scale was manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Interest was reignited when the health concerns of the then dominant cadmium-containing filler metals became known in the late 1970s, causing many companies to rapidly develop alternatives. Investigations conducted into various ternary and quaternary systems based on silver, copper and zinc, including: Ag-Cu-Zn-Ga [62], Ag-Cu-Zn-Ni [62], Ag-Cu-In [63], Ag-Cu-Sn [64] and Ag-Cu-Zn-Sn [62] eventually led to tin being selected as a suitable replacement for cadmium [65,66], with many manufacturers adopting filler metals of the Ag- Cu-Zn-Sn quaternary system. Eventually, legislation introduced in the European Union (Commission regulation (EU) No 494/2011) banned the sale of brazing filler metals with cadmium concentrations ≥ 0.01wt-% (barring specialist military and aerospace applications) [10].…”
Section: Silver-based Alloysmentioning
confidence: 99%
“…Interest was reignited when the health concerns of the then dominant cadmium-containing filler metals became known in the late 1970s, causing many companies to rapidly develop alternatives. Investigations conducted into various ternary and quaternary systems based on silver, copper and zinc, including: Ag-Cu-Zn-Ga [62], Ag-Cu-Zn-Ni [62], Ag-Cu-In [63], Ag-Cu-Sn [64] and Ag-Cu-Zn-Sn [62] eventually led to tin being selected as a suitable replacement for cadmium [65,66], with many manufacturers adopting filler metals of the Ag- Cu-Zn-Sn quaternary system. Eventually, legislation introduced in the European Union (Commission regulation (EU) No 494/2011) banned the sale of brazing filler metals with cadmium concentrations ≥ 0.01wt-% (barring specialist military and aerospace applications) [10].…”
Section: Silver-based Alloysmentioning
confidence: 99%
“…Compared with the brazing filler metals with high Ag, the low-Ag brazing filler metals have significant cost advantages, but the decrease in the content of Ag directly results in problems such as high melting points and poor flowability, which limit the application of low-Ag brazing filler metals in industries such as air conditioning, refrigerators, motors and instruments [9][10][11]. Some previous studies have revealed that any element that can decrease the melting temperature of the main element in the brazing filler metal can also decrease the melting point of the filler metal alloy [12][13][14]. The main elements in low-Ag brazing filler metal are Ag, Cu and Zn, with melting temperatures of 961.78 • C, 1083.4 • C and 419.53 • C, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers mainly improve the performance of the low-silver filler metals through "microalloying" [8], i.e., improving the performance of the filler metal by adding a small amount of an alloy element into a base filler metal. Based on the most widely used AgCuZn or AgCuZnSn low-silver filler metals, trace amounts of beneficial elements such as Ga, In, Mn, Ni, Li, and rare earth elements (RE) have been added to optimize the melting temperature, spreading performance, microstructure, and mechanical properties, to obtain low-silver filler metals with comparable properties to the traditional high-silver brazing filler metals [9].…”
Section: Introductionmentioning
confidence: 99%